Noncompleted Sexual Offenses: Internal States, Risks and Difficulties Related to Crime Commission through the Lens of Sexual Offenders. (March 2023) - Leclerc, Benoit; Wortley, Richard; Reynald, Danielle; Cook, Alana; Cale, Jesse
The study aims to generate insights from sexual offenders on the influence of internal states and how they perceive risks of apprehension and difficulties in the context of noncompleted sexual offenses, that is when offenders initiated the offense but were stopped or discouraged either before or during sexual contact. Adult males incarcerated for sexually offending completed a self-report questionnaire. Regression models, including interaction effects, were estimated. Two interaction effects were found providing insights into which and how internal states, such as intoxication to alcohol, may influence perceived difficulties related to crime. Future research should promote the investigation of noncompleted sexual offenses, which could provide a real opportunity to generate new or complementary insights for better understanding and guiding prevention initiatives.